Solidaritas Sosial dalam Perspektif Emile Durkheim dan Tantangannya di Era Digital - Akdila Bulanov M.Si; Dahlia; Etika hati; Siti Nela; Suci Indah Noprizuliani (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
The development of digital technology has significantly changed the patterns of social interaction in society. The presence of the internet and social media has created a new communication space that allows individuals to interact without geographical boundaries. However, this development also poses challenges to social solidarity, the foundation of social life. This article aims to examine the concept of social solidarity according to Émile Durkheim and analyze the various challenges that arise in the digital era. The method used is literature review by examining various relevant literature. The results of the study indicate that social solidarity remains a crucial element in maintaining social integration, facing various challenges such as individualism, social polarization, the spread of disinformation, and the decline in face-to-face interaction.